Relational, contractual or dual governance? An inwards look into a Chinese family business - Bin, Y.; António, N.; Xiao, W.; Trigo, V. (International Journal of Learning and Change, 2019)
Family businesses have been an important component of China's reform and opening since the early 1980s as well as the most widespread manifestation of entrepreneurship. Following the initial stage of 'pure entrepreneurship', most family businesses face the problem of how to optimise their governance structure, which needs to evolve from a relational model to a more institutionalised system. Through an in-depth study of a company established in 2003, this research addresses this issue by analysing the changes operated in its governance around a central question: which governance model should be adopted to integrate the dual needs of family's trust and the capabilities of non-family professional managers to maximise the interests of the family business and sustain its development? The research is based on a single case study and used face-to-face interviews, company documents and direct observation as the main sources of data collection. Findings show that, along its existence, the company continuously changed its governance model to adapt to the needs of a more efficient and effective management.